EXPLORING TEACHERS AND STUDENTS’ PERSPECTIVES TOWARD NEGOTIATED SYLLABUS IN ENGLISH LEARNING FOR SENIOR HIGH SCHOOL - Imam Ghozali; Banun Havifah Cahyo Khosiyono; Muhammad Ulil Abror (Journal of English for Academic and Specific Purposes, 2021)
Designing language syllabus is one of the important processes in the English language teaching contexts. Ensuring both teachers and students’ needs what and how their teaching and learning are applicable, negotiated syllabus can be proposed in teaching-learning processes. This study aims to find the teachers' and students' perspectives to determine whether aspects of the syllabus may be negotiable. Qualitative descriptive is used in this research. The participants involved were four English teachers and twenty students. Data were collected by using a questionnaire in the form of open-ended questions. The syllabus aspects that may be interested to negotiate according to Boon (2011) are course content, lesson aims, sequencing, material, homework, evaluation, methodology, groupings, and error correction. Both teachers and students believe the eleven areas could be negotiated. However, there are some debates in several areas. According to some teachers’ perspectives, the area of material, homework, evaluation, and error correction are not needed to be negotiated. Besides, according to some students, the area of course content, lesson aim, sequencing, material, grouping, and error correction are the teachers’ responsibilities.